2004
DOI: 10.1074/jbc.m402189200
|View full text |Cite
|
Sign up to set email alerts
|

Cns1 Is an Activator of the Ssa1 ATPase Activity

Abstract: Hsp90 is a key mediator in the folding process of a growing number of client proteins. The molecular chaperone cooperates with many co-chaperones and partner proteins to fulfill its task. In Saccharomyces cerevisiae, several co-chaperones of Hsp90 interact with Hsp90 via a tetratricopeptide repeat (TPR) domain. Here we show that one of these proteins, Cns1, binds both to Hsp90 and to the yeast Hsp70 protein Ssa1 with comparable affinities. This is reminiscent of Sti1, another TPR-containing co-chaperone. Unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…While direct biochemical evidence is lacking to confirm this hypothesis, strong indirect evidence exists in the form of biochemical analysis of equivalent DnaK mutations (Mayer et al 2001) and also the effect of Hsp40 and TPR cochaperones on ATPase stimulation of Ssa1p (Cyr et al 1992;Wegele et al 2003;Hainzl et al 2004). Promoting the interaction of Hsp70-Ssa with the prion substrate may disrupt the finely tuned ATPase hydrolysis cycle and thus prevent prion propagation by not releasing substrate for prion conversion.…”
Section: A176tmentioning
confidence: 99%
“…While direct biochemical evidence is lacking to confirm this hypothesis, strong indirect evidence exists in the form of biochemical analysis of equivalent DnaK mutations (Mayer et al 2001) and also the effect of Hsp40 and TPR cochaperones on ATPase stimulation of Ssa1p (Cyr et al 1992;Wegele et al 2003;Hainzl et al 2004). Promoting the interaction of Hsp70-Ssa with the prion substrate may disrupt the finely tuned ATPase hydrolysis cycle and thus prevent prion propagation by not releasing substrate for prion conversion.…”
Section: A176tmentioning
confidence: 99%
“…Proteins containing TPR domains with the dicarboxylate clamp in S. cerevisiae has also been shown to interact with molecular chaperones. Tom70 has been shown to interact with both Ssa1 and Hsc82 to facilitate protein import into mitochondrion (Young et al 2003 (Wegele et al 2003) and Cns1 (Hainzl et al 2004) are capable of stimulating the ATPhydrolytic activity of Ssa1. In this report, we demonstrated that a previously uncharacterized TPR-containing protein, Sgt2 (Kordes et al 1998), in S. cerevisiae has the capacity to interact with members of Ssa molecular chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…Ssa ATPase activity, and therefore protein folding capacity, is in turn governed by modulatory proteins such as the DnaJ homolog, Ydj1, which stimulates ATPase activity up to 10-fold, and Fes1, recently identified as a nucleotide exchange factor (11,12). In addition, Sti1 and Cns1, two tetratricopeptide repeat proteins associated with the Hsp90 chaperone complex, were recently demonstrated to strongly activate Ssa1 (13,14). Another pair of Hsp70 proteins in yeast, functionally distinct from the Ssa chaperones, are encoded by SSB1 and SSB2.…”
mentioning
confidence: 99%